2005
DOI: 10.3758/bf03193624
|View full text |Cite
|
Sign up to set email alerts
|

Distortions of perceived length in the frontoparallel plane: Tests of perspective theories

Abstract: The perceived length of a line segment in a frontoparallel plane is sometimes affected by the presence of other line segments in the visual field. Perspective theories attribute such interactions to sizeconstancy scaling: The configuration of line segments present in the visual field includes depth cues that trigger size scaling of each line segment. In three experiments, we test this claim for a range of simple configurations composed of two line segments joined at a point. These configurations include the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 28 publications
5
45
0
2
Order By: Relevance
“…We draw the reader's attention to an analogous finding in the literature on pictorial illusions of length in Wolfe, Maloney, and Tam (2005), who concluded that illusory distortions of perceived line length cannot be attributed to a single depth interpretation of the pictured scene. It is also plausible that the visual system has no consistent interpretation of such pictured scenes.…”
Section: Discussionmentioning
confidence: 92%
“…We draw the reader's attention to an analogous finding in the literature on pictorial illusions of length in Wolfe, Maloney, and Tam (2005), who concluded that illusory distortions of perceived line length cannot be attributed to a single depth interpretation of the pictured scene. It is also plausible that the visual system has no consistent interpretation of such pictured scenes.…”
Section: Discussionmentioning
confidence: 92%
“…The results demonstrated that the degree of vertical overestimation directly depended on the degree of asymmetry, reaching its maximum when the horizontal bisection was symmetric (inverted T conWguration) and its minimum when the two lines formed a L shape. More recently, Wolfe et al (2005) conducted an experiment very similar to that of Künnapas and they also observed that the symmetry or asymmetry of bisection determines the degree of vertical overestimation. Although none of the studies proposed theoretical accounts to support their data, they both showed that the symmetry of bisection was determinant in line length perception.…”
Section: Introductionmentioning
confidence: 88%
“…Several studies suggesting that the visual Weld's shape has an impact on the vertical bias, reported that the vertical overestimation is signiWcantly reduced under monocular viewing condition, in comparison to binocular viewing (Künnapas, 1957a, b;Prinzmetal & Gettleman, 1993). It has recently been concluded that the size-constancy scaling mechanisms and the visual Weld anisotropy have independent eVects on the vertical bias (Williams & Enns, 1996) but that none of the two theories could account for the amount of the vertical overestimation in some two-line conWgurations (see Wolfe et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prinzmetal & Gettleman, 1993) and, with regard to possible effects of phenomenal perspective (von Collani, 1985), Ward, Porac, Coren, and Girgus (1977) could not find substantial evidence for a three-dimensional (3D) interpretation of the ⊥-figure (cf. Wolfe, Maloney, & Tam, 2005, for a formal experimentum crucis). Although there have been several proposals for a general, neurophysiological account of visual illusions (e.g., Fermüller & Malm, 2004: neural noise; Ganz, 1964: lateral inhibition), none has picked Titchener's ⊥ as its prime example, or offered a detailed explanation of the ⊥-illusion.…”
mentioning
confidence: 99%